Penyuluhan Dan Pembuatan Ramuan Jamu Saintifik Hipertensi, Asam Urat, Kolesterol Dan Diabetes Melitus Pada Lansia Di Desa Tanggan, Kec. Gesi, Kab.Sragen - Suhesti, Iin; Setiyanto, Riyan; Marshanda, Camelia; oktaviani, Diah Ayu (Politeknik Indonusa Surakarta, 2025)
Degenerative diseases in the elderly are a significant health problem in Tanggan Village, Gesi District, Sragen Regency, with the majority of the population (70%) working as farm laborers. Economic limitations make access to health services a challenge, while public knowledge about processing natural ingredients into scientific herbal concoctions is still minimal. This community service activity aims to improve public knowledge and skills in making scientific herbal concoctions to treat hypertension, gout, cholesterol, and diabetes mellitus. The methods used include lectures, demonstrations, and discussions involving 35 elderly people. The results of the activity showed an increase in participants' knowledge about the concept of scientific herbal medicine, with 90% of participants being able to answer questions related to the material presented. Participants also succeeded in practicing making scientific herbal concoctions according to the recommended dosage. This activity has a positive impact on increasing community independence to maintain health through the use of scientifically processed herbal ingredients, as well as reducing dependence on chemical drugs.